PENGEMBANGAN BUKU ELEKTRONIK (E-BOOK) PRAKARYA ELEKTRONIKA UNTUK MENINGKATKAN KETERAMPILAN ABAD 21 TERINTEGRASI KETERAMPILAN BERPIKIR KREATIF MAHASISWA - Yaspin Yolanda (Universitas Islam Sumatera Utara, 2022)
This research started with the absence of E-Books that facilitate students in improving their creative thinking skills, the low cognitive understanding of students about relay components, infrared sensors and Arduino Uno need to be taught to students as new knowledge in the development of robotic-based technology, as well as students' weak skills in make electronics. This study aims to describe students' creative thinking skills. The research subjects were physics education students at PGRI Silampari University, from August 2022 to. January 2023. Kemp's model is used in this research and development. Diagnostic instruments in the form of tests and non-tests. Analysis using descriptive. The results of the study show that this E-Book is valid and practical so that it can facilitate students to work on electronics projects using relay modules, infrared sensors and Arduino Uno modules in assessing creative thinking skills with an average achievement of creative thinking skills of 58.9% of developing students. as expected, 15.6% developed and 13.3% started to develop and 12.2% did not develop.